Child malnutrition study - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Child malnutrition is an early warning signal of instability. Recent research in Nigeria by CGIAR Climate Security shows that tracking rates of wasting can help predict where social tensions could erupt next. The researchers discovered that rising temperatures don’t trigger violence overnight. Instead, they quietly erode food systems until children begin to waste away and that’s when communities start to fracture.